Assessment On The Socio-Economic Benefits of Zakat Among Muslims in Kaduna State Nigeria - Suleiman, Muhammad; Hamza, Musa (Research and Community Service Institute (LP2M) of Institute Pesantren Sunan Drajat, 2025)
This work titled “Assessment on the Socio-Economic Benefitsof Zakat among Muslims in, Kaduna State”, the study discussed on five chapters, chapter one discussed on Background of the study, statement of the problem, aims and objective of the study, significant of the study etc. The study was guided by five research questions. The study was limited to people living in Kaduna State. A survey design was employed for conducting the research. A sum of 200 respondents was randomly selected and questionnaire was administered, the data was analyzed using frequency counts and percentage. Base on the recommendation it shows;Establish and empower Zakat boards or agencies at both local and national levels to standardize the collection, management, and distribution of Zakat. Religious scholars, NGOs, and Islamic centers should organize regular programs to educate Muslims on the importance, calculation, and distribution of Zakat. The government should consider recognizing and supporting Zakat as part of the.